Sensititre autoreader for same-day breakpoint broth microdilution susceptibility testing of members of the family Enterobacteriaceae. - Doern, G V (1987)
The Sensititre Autoreader system is an instrument-assisted broth microdilution susceptibility test procedure based on the detection of fluorogenic growth substrate metabolism by test bacteria with different concentrations of antimicrobial agents. In the current investigation, this system was assessed as a means for predicting the in vitro activity of 17 antimicrobial agents versus numerous species of the family Enterobacteriaceae and Pseudomonas aeruginosa by using a breakpoint broth microdilution test format. Same-day and overnight determinations of susceptibility were made with the Sensititre Autoreader system, and in both cases, the results were compared with those obtained with a manual overnight breakpoint broth microdilution susceptibility test. Among a total of 6,086 organism-antimicrobial agent comparisons with Enterobacteriaceae, concordance was noted between the results of the same-day Autoreader system and the manual overnight test in 94.4% of cases. The same-day Autoreader results with members of the Enterobacteriaceae other than Proteus spp. were determined after 4 h of incubation; with Proteus spp. the same-day Autoreader results were determined after 5 h of incubation. When the Enterobacteriaceae Autoreader results were determined after 18 h of incubation, concordance was noted in 97.2% of comparisons. Among a total of 1,377 organism-antimicrobial agent comparisons with P. aeruginosa after 18 h of incubation, agreement of results from the manual overnight test and the Autoreader system was achieved in 92.2% of cases.